The Role of Business Strategy in Moderating the Influence of Management Control Systems and Environmental Uncertainty on Managerial Performance - Sabaruddinsah, Sabaruddinsah; Asiah, Neng (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to determine the influence of management accounting information systems, environmental uncertainty on managerial performance and whether business strategy can moderate the relationship between management accounting information systems and environmental uncertainty on performance. The research method uses a quantitative approach, with a research population of UMKM manufacturing companies in Bekasi City with a sampling technique using purposive random sampling. The data analysis technique uses Partial Least Square ( SEM) PLS. The results of this study indicate that management accounting information systems and environmental uncertainty have a positive and significant effect on performance, while business strategy does not moderate the relationship between management accounting information systems and environmental uncertainty on managerial performance.